2022
DOI: 10.1039/d1fo03770f
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols alleviate the adverse effects of diabetes on oocyte quality

Abstract: Maternal diabetes mellitus reduces oocyte quality, such as abnormalities of spindle assembly and chromosome segregation, mitochondrial dysfunction, decrease of fertilization rate, increase of ROS, and so on. So, it’s important...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2023 nols can also alleviate mitochondrial dysfunction and DNA damage and improve the oocyte-maturation rate. 113 Similar findings showed that EGCG could be used to improve the quality of diabetic oocytes at a dose of 30 μM, at least in vitro. 114 4.1.9.…”
Section: Food and Function Reviewmentioning
confidence: 69%
“…This journal is © The Royal Society of Chemistry 2023 nols can also alleviate mitochondrial dysfunction and DNA damage and improve the oocyte-maturation rate. 113 Similar findings showed that EGCG could be used to improve the quality of diabetic oocytes at a dose of 30 μM, at least in vitro. 114 4.1.9.…”
Section: Food and Function Reviewmentioning
confidence: 69%
“…Therefore, patients with diabetes might have a declined oocyte maturation rate and low-quality oocytes, which may be more severe in the infertile patients with diabetes. It has also been reported that oocytes of the mouse with type 1 diabetes showed high level of ROS, abnormal spindle assembly and chromosome alignment, mitochondrial dysfunction and alterations of histone acetylation [ 3 5 ]. In addition, the mitochondrial dysfunction and apoptosis can also be observed in cumulus cells of diabetic mouse [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, overcoming the problems correlated with IVM by optimizing the IVM system is of significant importance. Previous studies have shown that supplementation of antioxidants during the IVM process could improve the oocyte quality and reduce the damage caused by oxidative stress [ 5 , 14 , 15 ]. In line with this finding, we aimed to explore novel strategies to improve the maturation rate and quality of IVM oocytes of patients suffering from diabetes, thereby increase the assisted reproductive efficiency and ultimately improve the reproductive outcomes of these patients.…”
Section: Introductionmentioning
confidence: 99%